Postoperative Cognitive Dysfunction after Coronary Artery Bypass Grafting - Yuan,Shi-Min (2019)
Abstract Postoperative cognitive dysfunction is a common complication following cardiac surgery. The incidence of cognitive dysfunction is more pronounced in patients receiving a cardiac operation than in those undergoing a non-cardiac operation. Clinical observations demonstrated that pulsatile flow was superior to nonpulsatile flow, and membrane oxygenator was superior to bubble oxygenator in terms of postoperative cognitive status. Nevertheless, cognitive assessments in patients receiving an on-pump and off-pump coronary artery bypass surgery have yielded inconsistent results. The exact mechanisms of postoperative cognitive dysfunction following coronary artery bypass grafting remain uncertain. The dual effects, neuroprotective and neurotoxic, of anesthetics should be thoroughly investigated. The diagnosis should be based on a comprehensive cognitive evaluation with neuropsychiatric tests, cerebral biomarker inspections, and electroencephalographic examination. The management strategies for cognitive dysfunction can be preventive or therapeutic. The preventive strategies of modifying surgical facilities and techniques can be effective for preventing the development of postoperative cognitive dysfunction. Investigational therapies may offer novel strategies of treatments. Anesthetic preconditioning might be helpful for the improvement of this dysfunction.